Inhibition of G-protein signalling in cardiac dysfunction of intellectual developmental disorder with cardiac arrhythmia (IDDCA) syndrome. Issue 12 (10th November 2020) - De Nittis, Pasquelena; Efthymiou, Stephanie; Sarre, Alexandre; Guex, Nicolas; Chrast, Jacqueline; Putoux, Audrey; Sultan, Tipu; Raza Alvi, Javeria; ur Rahman, Zia; Zafar, Faisal; Rana, Nuzhat; Rahman, Fatima; et al.
Abstract : Background: Pathogenic variants of GNB5 encoding the β5 subunit of the guanine nucleotide-binding protein cause IDDCA syndrome, an autosomal recessive neurodevelopmental disorder associated with cognitive disability and cardiac arrhythmia, particularly severe bradycardia. Methods: We used echocardiography and telemetric ECG recordings to investigate consequences of Gnb5 loss in mouse. Results: We delineated a key role of Gnb5 in heart sinus conduction and showed that Gnb5 -inhibitory signalling is essential for parasympathetic control of heart rate (HR) and maintenance of the sympathovagal balance. Gnb5 −/− mice were smaller and had a smaller heart than Gnb5 +/+ and Gnb5 +/−, but exhibited better cardiac function. Lower autonomic nervous system modulation through diminished parasympathetic control and greater sympathetic regulation resulted in a higher baseline HR in Gnb5 −/− mice. In contrast, Gnb5 −/− mice exhibited profound bradycardia on treatment with carbachol, while sympathetic modulation of the cardiac stimulation was not altered. Concordantly, transcriptome study pinpointed altered expression of genes involved in cardiac muscle contractility in atria and ventricles of knocked-out mice. Homozygous Gnb5 loss resulted in significantly higher frequencies of sinus arrhythmias. Moreover, we described 13 affected individuals, increasing the IDDCA cohort to 44 patients. Conclusions: Our data demonstrate that loss of negative regulation of the inhibitory G-protein signalling causes HR perturbations in Gnb5 − /− mice, an effect mainly driven by impaired parasympathetic activity. We anticipate that unravelling the mechanism of Gnb5 signalling in the autonomic control of the heart will pave the way for future drug screening.